2016
DOI: 10.1002/slct.201601544
|View full text |Cite
|
Sign up to set email alerts
|

Graphene Derivative As a Highly Efficient Nitrosonium Source: A Reusable Catalyst for Diazotization and Coupling Reaction

Abstract: An efficient and a simple approach for the synthesis of azo dyes have been developed by the diazo coupling reactions of active aromatic compounds in the presence of in‐situ nitrite functionalized graphene oxide polyvinyl alcohol GO‐PVA composite as a highly efficient nitrosonium ion source. This methodology was objected to defeat the limitations of the earlier reported method such as use of acids, alkalis and toxic solvents, to reduce the stability of diazonium salts at room temperature, modest yields and long… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 48 publications
0
22
0
Order By: Relevance
“…[54] TheS N-rGO has an I D /I G ratio of 1.06, signifying that the doping of Sa nd N produces defects in the carbon framework. [9] The SN-rGO O1sX PS spectrum (Figure 5c)r eveals the remaining oxygen bindings in the material. The XPS survey scans of GO andS N-rGO werec ompared;t he GO sheets show the presenceo fo nly Ca nd O atoms (Figure 5a).…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations
“…[54] TheS N-rGO has an I D /I G ratio of 1.06, signifying that the doping of Sa nd N produces defects in the carbon framework. [9] The SN-rGO O1sX PS spectrum (Figure 5c)r eveals the remaining oxygen bindings in the material. The XPS survey scans of GO andS N-rGO werec ompared;t he GO sheets show the presenceo fo nly Ca nd O atoms (Figure 5a).…”
Section: Resultsmentioning
confidence: 89%
“…The CÀOp eak intensity is significant because of the oxidation of the natural graphite powdert oG O. [9] The SN-rGO O1sX PS spectrum (Figure 5c)r eveals the remaining oxygen bindings in the material. The three peaks appeareda t5 31.1, 532.2, and5 34.2 eV for C=O, OÀC=O, and CÀO, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The TGA curve of GO showed that it is thermally unstable and weight loss occurred at three stages. The higher weight loss is observed at about 58% near about 100 °C to 200 °C, which is due to the decomposition of trapped water molecule, while second stage observed about 68% mass loss near 250 °C, which is due to other functionalized group . Third stage showed about 90% weight loss at 650 °C because of the pyrolysis of the remaining oxygen functionalized groups as well as burning of aromatic ring carbon .…”
Section: Resultsmentioning
confidence: 94%
“…GO and G@SiO 2 -AR (Table S1) shows low C/O ratio 2.07 and 1.1, respectively, which is quite less as compared to GO. The high resolution C1s spectrum of GO ( Figure S3) showed carbon atom in various functionalities such as CÀ C (283.5 eV), C=C/ CÀ O bond (286.7 eV) and carboxylate carbon C=O (OH) (288 eV) [48] ( Figure S3). The high-resolution C 1s spectra of both adsorbents show the presence of 284.4 eV due to the CÀ C/À CÀ SiÀ bonds, 286.3 eV due to C=C/CÀ O bonds while 288.8 eV is for C=O bond (Figure 3b).…”
Section: Resultsmentioning
confidence: 99%